Towards a model to predict macular dichromats naming errors: Effects of CIE saturation and dichromatism type. - Moreira, Humberto; Caballero, Aurora; Lillo, Julio; Vitini, Isaac (The Spanish Journal of Psychology, 2001)
Sin resumen